The Effect of Antioxidant Administration on Semen Quality in Men with Infertility: A Randomized Placebo-Controlled Clinical Trial - Pinelopi Ioannidou; Theodosia Zeginiadou; Christos Venetis; Dimitrios Papanikolaou; Leonidas Zepiridis; Despoina Savvaidou; Katerina Chatzimeletiou; Alexandros Lambropoulos; Dimitrios G. Goulis; Grigoris Grimbizis; Efstratios M. Kolibianakis (Antioxidants)
A randomized, placebo-controlled, quadruple-blind trial was performed to evaluate the effect of oral administration of the antioxidant combination Spermotrend® for three months on semen quality in infertile men with at least one abnormal variable in semen analysis. Eighty men were randomized between 2019 and 2022, receiving either the antioxidant combination Spermotrend® (n = 40, spermotrend-group) or placebo (n = 40, placebo-group). Although a total of 80 patients were enrolled in the study, the final data is only from 70 patients. The primary outcome measure was sperm motility (rapid progressive, progressive, and total motility). The values of primary and secondary outcomes between treatment initiation and treatment completion were compared within groups. Moreover, their changes between treatment initiation and treatment completion were compared between the placebo- and the spermotrend-groups. Sperm rapid progressive motility significantly increased in infertile men treated for three months with antioxidant combination Spermotrend® (+1.0%, 95% CI: 0.0 to +2.0, p = 0.04), while this increase was not observed in the placebo-group. Sperm progressive motility significantly increased in infertile men treated for three months with antioxidant combination Spermotrend® (+3.0%, 95% CI: 0.0 to +15.1, p = 0.02), while this increase was not observed in the placebo-group. Similarly, DFI was significantly decreased in infertile men treated for three months by antioxidant combination Spermotrend® (−3.2%, 95% CI: −5.8 to −0.5, p = 0.02). However, no statistically significant differences were observed in the changes of pre- and post-treatment values between the spermotrend- and the placebo-group regarding sperm progressive motility, concentration, normal morphology, DFI, and formation of 8-OH-dG. The antioxidant combination Spermotrend® appears to exert limited benefit on sperm motility and DFI in infertile men with at least one abnormal variable in semen analysis.